Compressive behavior assessment of a newly developed circular cell-based lattice structure. (July 2021) - Alomar, Zaki; Concli, Franco
Graphical abstract: Highlights: Development of a new type of lattice structure based on a circular constituent cell. The new cell exhibits high load-bearing capacity with stretch dominating behavior. Upon compression, the stress is evenly distributed across all the layers of the new lattice structure. The circular lattice structure failed in a layer-wise crushing manner without exhibiting any plateau region. Application-wise, the new type of lattice structure exhibits a favorable behavior for shock absorption applications. Abstract: Designing new lattice structures falls under the same category of defining a new material, owing to their unique properties and superior characteristics. The development of Metal Additive Manufacturing (MAM) technology alleviates almost all limitations associated with the geometrical shapes and the design complexity. Herein, the capability of the selective laser melting (SLM) process was employed to design a new type of lattice structure made of Ti6Al4V with a circular-based constituent cell. The new circular cell-based lattice structure was manufactured with three wall thicknesses along with Body-Centered Cubic (BCC) lattices with equivalent struts' diameters for comparison reason. Preliminary numerical simulations and quasi-static compression tests were carried out to determine the mechanical properties and the deformation mechanism of the two sets of lattices. Then, performance comparison with other types of lattices was accomplished via mechanical properties-relative density plots. The numerical results showed an evenly distributed stress within the microstructures of the circular cells. Additionally, the new cell exhibited higher load-bearing capacity and stiffness in comparison with the BCC cell of higher relative density. A crushing failure mechanism with a significant stress recovery was observed upon the collapse of each layer of the circular cells which is ideal for shock-absorption applications.